Serotonin and aggressive motivation in crustaceans: Altering the decision to retreat - Huber, Robert (The National Academy of Sciences of the USA, 1997)
In crustaceans, as in most animal species, the amine serotonin has been suggested to serve important roles in aggression. Here we show that injection of serotonin into the hemolymph of subordinate, freely moving animals results in a renewed willingness of these animals to engage the dominants in further agonistic encounters. By multivariate statistical analysis, we demonstrate that this reversal results principally from a reduction in the likelihood of retreat and an increase in the duration of fighting. Serotonin infusion does not alter other aspects of fighting behavior, including which animal initiates an encounter, how quickly fighting escalates, or which animal eventually retreats. Preliminary studies suggest that serotonin uptake plays an important role in this behavioral reversal.